Variations of nutrient concentrations and contents between summer and autumn within tree compartments of European beech (Fagus sylvatica). Issue 6 (29th September 2016) - Ulbricht, Matthias; Göttlein, Axel; Biber, Peter; Dieler, Jochen; Pretzsch, Hans
Abstract: The paradigm of sustainable forest management was initially aimed to ensure continuous wood supply but has gradually been extended for many functions and services of forest ecosystems, including the aspect of nutrient sustainability. The current tendency towards harvesting all year round and whole‐tree export for energy purposes raised the question of how the input : output balance of nutrients depends on site conditions, tree species, and harvest intensity. Possible differences in nutrient export between harvesting in autumn and summer have been more or less neglected. Based on compartment‐wise analyses of biomass and nutrient (Ca, K, Mg, and P) concentrations of adult European beeches ( Fagus sylvatica [L.]), nine compartments were sampled in summer and nine in autumn. We found, for the majority of the compartments (especially in branch wood), increased levels of nutrient concentrations: 81% (Ca), 54% (K), 90% (Mg), and 96% (P) in autumn compared to summer. Upscaling our results to stand level revealed up to 10.0% and 1.6% less mineral nutrient exports of Ca and Mg, respectively, for whole‐tree harvest in forest stands when carried out in summer instead of autumn. Nutrient removal was increased by 0.8% and by 13.0% for K and P, respectively, in summer. Despite lower nutrient export, many ecological, logistic, and technical reasons discourage harvesting in summer. Our findings, however, deliver an additional yet so far missing mosaic piece for a better understanding and assessment of the frame conditions for sustainable nutrient management in beech forests.